Further Investigation Evaluating the Effect of Dietary Chromium Propionate and Yucca schidigera Supplementation in Finishing Pig Diets - J. T. Gebhardt; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. A. Loughmiller; A. L. de Souza; M. J. Rincker; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 2,430 pigs (PIC 359 × 1050; initial BW = 64.6 lb) were used to evaluate the effects of dietary chromium propionate (Cr; KemTRACE Cr, Kemin Industries, Des Moines, IA) and aYucca schidigera-based extract (Micro-Aid; DPI Global, Porterville, CA) on growth performance of finishing pigs housed in commercial conditions. Pigs were placed in balanced, mixed-gender pens (27 pigs per pen), blocked by average pen BW, and randomly assigned to treatment. Diets were corn-soybean meal-based and were formulated in 5 dietary phases to meet or exceed NRC6 requirement estimates. Dietary treatments were fed for the full duration of the study and were arranged in a 2 × 3 factorial with 14 pens per treatment. Main effects included chromium (0 or 200 ppb added Cr), andYucca schidigeraextract (0, 62.5, or 125 ppm active ingredient). For the overall study, a marginally significant (linear; P ≤ 0.072) Cr ×Yucca schidigerainteraction was observed for ADG and ADFI. Pigs fedYucca schidigerawithout added Cr had similar ADG and ADFI; however, pigs fed added Cr had increased ADG and ADFI asYucca schidigeraincreased from 62.5 to 125 ppm. Added Cr had no effect on F/G (P>0.05). IncreasingYucca schidigeraresulted in a marginally significant poorer (quadratic; P = 0.057) F/G. The main effect of addedYucca schidigeraon final BW (quadratic; P = 0.012) resulted in pens which were supplemented with 62.5 ppm having the lowest final BW. Carcass characteristics, including HCW, loin depth, backfat, percentage lean, and percentage yield, were not influenced by added Cr (P ≥ 0.278). AddedYucca schidigeradid not influence loin depth, backfat, percentage lean, or percentage yield (P ≥ 0.152). In summary, adding Cr propionate along withYucca schidigeraled to modest changes in performance, with the greatest benefit observed with 200 ppb Cr and 125 ppm (active ingredient) Yuccaschidigera.
Keywords: chromium propionate; finishing pigs; Yucca schidigera